Potential Utilization of White Snapper (Lates calcalifer BLOCH, 1790) landed at the Fishing Port of Merauke Regency South Papua - Marius Agustinus Welliken; Sajriawati Sajriawati; Istikomah Istikomah (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
This study aims to determine the sustainable potential, the level of utilization, the number of catches of barramundi allowed to be caught in Merauke Regency. This research was conducted from January to February 2022. Data analysis used in this study were: CPUE, Standardization of fishing effort, Estimation of sustainable potential (MSY) and Optimum Effort, Analysis of utilization and effort levels. The results of this study show that the Potential (Maximum Sustainable Yield) of barramundi (Lates calcalifer Bloch, 1790) in the Merauke PPN is 289,183 tons with an effort of 27 trips, the utilization rate of barramundi in 2015 to 2021 the value of the utilization rate of barramundi resources has experienced increase, the number of catches using the production surplus method in the 718 Fisheries Management area in 2015-2021 results in a maximum sustainable potential value (MSY) of barramundi of 289,183 Kg, while the optimum fishing effort is 27 trips. Based on the research results, barramundi fishing efforts must be controlled and limited because from 2015 – 2021 the JTB (Allowed Catch) value has passed, namely 23,805 Kg, but it is still not overfishing because it has not exceeded the threshold value for Sustainable Production (MSY) 289,183 Kg.